Dampak Kemiskinan Terhadap Anak Yang Bekerja di Kota Batam Implikasi pada Angka Putus Sekolah (APS) - Mas’ud Zein; Trian Zulhadi (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2019)
This study entitled The Impact of Poverty on Child Labor in Batam Island Implications for children dropping out of school. This study aims to determine how the influence of poverty from the characteristics of Household, Child Characteristics and Residential Characteristics on children working in Batam Island and the Implications on Children Drop Out (APS). The results of this study obtained both descriptively and quantitatively is there is a positive significant relationship that poverty seen from the characteristics or characteristics of the head of Household (KRT), Child Characteristics (KA) and Residential Characteristics (KTT) selected as a proxy in research is in influencing the participation of children who work to help parents in meeting the needs of everyday life and implicate the high school dropout (APS) in the city of Batam.